2020
DOI: 10.15294/jdm.v11i2.23499
|View full text |Cite
|
Sign up to set email alerts
|

Managing Human Resources Management Policies in a Private Hospital and its Impact on Work-Life Balance and Employee Engagement

Abstract: This study examines the role of human resources practice in enhancing work-life balance and engagement. We try to identify how are employees manage their work and life with the help of an organization to achieve stronger engagement. Data obtained by distributing a questionnaire to 200 employees from a private hospital in Banyuwangi. The collection of the questionnaire took 45 days and we have 113 useable responses. The technique used is mediation analysis using bootstrapping analysis. The results showed there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Human resources with awareness of environmental sustainability become the focus in the Green HRM paradigm. In a study conducted by Luturlean et al (2020), it was found that the implementation of GHRM involves human resources that care about the green environment. This includes attitudes and actions that support environmentally friendly practices, such as efficient energy use, waste reduction, and increased environmental awareness in the workplace.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Human resources with awareness of environmental sustainability become the focus in the Green HRM paradigm. In a study conducted by Luturlean et al (2020), it was found that the implementation of GHRM involves human resources that care about the green environment. This includes attitudes and actions that support environmentally friendly practices, such as efficient energy use, waste reduction, and increased environmental awareness in the workplace.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Training and development represent all practices that can have a significant impact on employee performance (Kanyua, 2021). Work-life balance is known as a condition in which there is only a small level of conflict between work and personal/family needs (Luturlean et al, 2020). Corporate social responsibility is practices that send signals and signals that an organization cares and cares and understands the value of employees (Farouk & Jassim Al-Din, 2014).…”
Section: Literature and Hypotheses Development 21 Employer Brandingmentioning
confidence: 99%
“…The intricate dynamics between HRM policies and employee experiences have evolved as a central theme in modern organizational studies. Luturlean et al (2020) provide a sectorspecific lens by examining private hospitals. Their study underscores the idea that the healthcare sector, with its unique pressures and challenges, necessitates robust HRM policies.…”
Section: Introductionmentioning
confidence: 99%